DIABETIC FOOT ULCER DUE TO TRAUMA AFTER MOTORCYCLE ACCIDENT: A CASE REPORT - Achmad Fauji; Uswatun Hasanah; Nur Miladiyah Rahmah; Puji Astuti; Rika Harini (Menara Medika, 2026)
Introduction: Diabetic foot ulcer due to trauma is serious complications that can lead to severe infections and even amputation, especially if treatment is delayed. Purpose: This case presentation to describe comprehensive wound management using evidence based and culturally adapted intervention in a traumatic diabetic ulcer. Method: A case report of a 40-year-old man who suffered a laceration on his left heel due to a traffic accident progressing to infected ulcer. Wound care was conducted using TIME CDST assessment, autolytic debridement, modern dressing with chitosan-zinc oxide ointment, and wound cleansing with boiled guava leaf (Psidium guajava) solution. The nursing diagnosis raised was impaired skin/tissue integrity. Result: Progressive wound healing was observed within two months, characterized by infection control, reduction of slough, increased granulation and epithelialization, and complete wound closure. Discussion: These findings suggest that combination of evidence-based wound care and culturally contextual herbal intervention demonstrated desirable outcomes. Early health education, structured monitoring, and documentation are crucial in preventing complications of chronic wounds in diabetic patients with trauma-related wounds.